2010
DOI: 10.1029/2010jd014595
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of summer northwest Pacific climate in 11 coupled model hindcasts: Local and remote forcing

Abstract: [1] The skills of 11 coupled ocean-atmosphere general circulation models (CGCMs) are investigated in the prediction of seasonal rainfall and circulation anomalies over the northwest (NW) Pacific for the period 1980-2001, with a focus on the summer following the mature phase of El Niño (hereafter JJA(1)). It is shown that the first empirical orthogonal function (EOF) mode of sea level pressure is closely tied to the second EOF mode of rainfall variability over the NW Pacific during JJA(1), indicative of strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 60 publications
3
78
1
1
Order By: Relevance
“…Therefore, though not the only factor, the TIO warming plays a very important role in WNP circulation change. In addition, muti-model results confirm the aforementioned conclusion (Chowdary et al, 2010).…”
Section: Conclusion and Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore, though not the only factor, the TIO warming plays a very important role in WNP circulation change. In addition, muti-model results confirm the aforementioned conclusion (Chowdary et al, 2010).…”
Section: Conclusion and Discussionsupporting
confidence: 78%
“…Serials of studies found that the TIO warming is triggered by ENSO and that the warming is induced by ocean dynamics and local air-sea interaction (Huang and Kinter, 2002;Xie et al, 2002;Du et al, 2009;Xie et al, 2009). Indeed, ENSO does not affect the WNP rainfall directly and that ENSO-induced TIO SSTA in the following summer is an important direct factor (Yang et al, 2007;Xie et al, 2009;Chowdary et al, 2010Chowdary et al, , 2011. A coupled general circulation model, which has quite good predicting skill, is used to analyse the relative role of TIO (Chowdary et al, 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recognized that the variability and changes of the Indian Ocean sea surface temperature (SST) play an important role in climate variability worldwide including Asian summer monsoon (e.g., Abram et al 2008;Schott et al 2009), Northwestern Pacific climate (e.g., Chowdary et al 2010;Xie et al 2009), the African Sahel drying trend (e.g., Giannini et al 2003), and El Niño and Southern Oscillation (ENSO) (e.g. Yu et al 2002;Luo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, some of them reported difficulties to predict summer mean precipitation anomalies in northwestern Asian monsoon events even for a 0-month lead forecast, although they are capable of predicting zonal wind anomalies at 850 hPa several months ahead and, consequently, satisfactorily predict summer monsoon circulation (Lee et al, 2011). A computationally feasible approach in order to accomplish reasonable predictions on a seasonal timescale is through ensemble forecasting in which several model forecasts are performed by introducing perturbations in the initial conditions or in the models themselves (Kalnay, 2003;Chowdary et al, 2010).…”
Section: Introductionmentioning
confidence: 99%